ANALISIS EFISIENSI EKONOMIS PENGGUNAAN FAKTOR PRODUKSI USAHATANI PADI ORGANIK DI DESA SIMBUR NAIK KECAMATAN MUARA SABAK TIMUR KABUPATEN TANJUNG JABUNG TIMUR - Frendy Sidauruk, Rian; Malik, Adlaida; Fitri, Yanuar (Universitas Jambi, 2019)
Organic rice farming is a farming that cannot be separated in relation with use of factors that affect production. In order achieve high production, then the production factor used must be optimized. This research aimed to know (i) the general overview of organic rice farming in Simbur Naik village, sub-district of Muara Sabak Timur, Tanjung Jabung Timur Regency. (ii) To determine the effect of productions factors on production on organic rice in Simbur Naik village, sub-district of Muara Sabak Timur, Tanjung Jabung Timur Regency, (iii) To analyze the economic efficiency of the use of production factors on the production of organic rice farming in Simbur Naik village, sub-district of Muara Sabak Timur, Tanjung Jabung Timur Regency. This reserach was done from Agustus 30th to September 19th 2017. Production function of Cobb Douglas was used to to know the effect of of the use of seed production factor, manure, Petrobios fertilizer, liquid organic fertilizer, urine pesticide, and labor as independent variables. Economic efficiency was used to evaluate the use of production factors. The data were obtained from 48 selected respondents by using census method. This reserach show that (i) in doing farming business, the farmer in Simbur Naik village could only carry out the rice cultivation process once a year and they used organic fertilizer as used in organic farming generally, namely manure or farmers also used petrobios fertilizer and liquid organic pertilizer.